Strong turbulent flow in the subauroral region in the Antarctic can deteriorate satellite-based navigation signals - Kotova, D. S.; Sinevich, A. A.; Chernyshov, A. A.; Chugunin, D. V.; Jin, Y.; Miloch, W. J. (Scientific Reports, 2025)
In the subauroral zone at the boundary of the auroral oval in the evening and night hours during geomagnetic disturbances, a narrow (about 1°–2°) and extended structure (several hours in longitude) is formed. It is known as a polarization jet (PJ) or the subauroral ion drift (SAID). The PJ/SAID is a fast westward ion drift and is one of the main signatures of a geomagnetic disturbance in the subauroral ionosphere at the altitudes of the F-layer, when the geomagnetic AE index reaches more than 500 nT. Plasma speed in the PJ/SAID can reach several kilometres per second, and the size of plasma irregularities inside it can reach scales from tens of meters to several hundred meters. Such high velocities and structured plasma can affect trans-ionospheric radio waves and lead to scintillations in the received signal. We show that at the moment of auroral activity intensification, an increase in the magnitude of phase scintillation index (σϕ) as well as loss of satellite signals lock were observed in the region of the PJ/SAID equatorward of the auroral oval over Dronning Maud Land (Queen Maud Land) in Antarctica. We find that fluctuations inside the PJ/SAID can lead to serious deterioration of radio communication or navigational services. We emphasize the importance of considering the geometry of the beam passing from the GNSS satellite to the receiver on the ground. We highlight the mutual contribution of the PJ/SAID and the diffuse aurora boundary, which are almost impossible to separate in practice. Our results demonstrate the importance of considering the subauroral zone, where very dynamic plasma formations can occur with a strong flow and various-scale irregularities inside that lead to serious interference in satellite communications.
Keywords: Dronning Maud Land; aurora; fysikk; geomagnetiske stormer; ionosfæren; magnetosfæren; romfysikk; sørlys

Ionosfæriske scintillasjoner på GNSS-signaler over Dronning Maud Land, Antarktis: statistikk og kasusstudier - Skjæveland, Arnlaug Høgås (Universitetet i Oslo, 2020)
I denne oppgaven er forekomsten av fasescintillasjoner på GNSS-signaler over deler av Dronning Maud Land i Antarktis kartlagt, ved bruk av scintillasjonsmottakere på Troll stasjonen (geografiske koordinater: 72.0◦S, 2.5◦Ø, magnetiske koordinater: 62.8◦S, 47.8◦Ø) og SANAE IV (geografiske koordinater: 71.7◦S, 2.8◦V, magnetiske koordinater: 62.0◦S, 45.0◦Ø). Ionosfæren i dette området er lite studert tidligere, og dette er de første resultatene som presenteres fra det nylig etablerte Troll ionosfæriske observatoriet. Den første delen av oppgaven er en statistisk studie hvor forekomsten av scintillasjoner i 2018 er kartlagt. Hovedfunnet i denne studien er at høye fasescintillasjoner kun forekommer ved høy geomagnetisk aktivitet, forekomsten av scintillasjoner er høyere postmidnatt enn premidnatt og at scintillasjoner forekommer både innenfor og nord for den statistiske auroraovalen. I denne oppgaven er det også gjennomført to kasusstudier, en fra februar 2018 og en fra mars 2018. Kasusstudiene brukte satellittdata fra solvinden, Swarm, DMSP og bakkebaserte instrumenter: scintillasjonsmottakere, magnetometere og Superdarn, fra både den nordlige og sørlige halvkule. Hovedfunnene fra kasusstudiene er at scintillasjoner på Troll og Sanae kan assosieres med partikkelnedbør, sterke vestgående strømmer og høye konveksjonshastigheter. De viste også en hvis symmetri i forekomsten av scintillasjoner, men scintillasjonene var kraftigere og var til stede over en lengre tidsperiode i Antarktis enn på Færøyene.
Keywords: Antarktis; Dronning Maud Land; Troll forskningsstasjon; aurora; geomagnetiske stormer; ionosfæren; romfysikk; sørlys

Mesospheric Nitric Acid Enhancements During Energetic Electron Precipitation Events Simulated by WACCM-D - Orsolini, Yvan J.; Smith-Johnsen, Christine; Marsh, Daniel R.; Stordal, Frode; Rodger, Craig J.; Verronen, Pekka T.; Clilverd, Mark A. (Journal of Geophysical Research: Atmospheres, 2018)
While observed mesospheric polar nitric acid enhancements have been attributed to energetic particle precipitation through ion cluster chemistry in the past, this phenomenon is not reproduced in current whole-atmosphere chemistry-climate models. We investigate such nitric acid enhancements resulting from energetic electron precipitation events using a recently developed variant of the Whole Atmosphere Community Climate Model (WACCM) that includes a sophisticated ion chemistry tailored for the D-layer of the ionosphere (50–90 km), namely, WACCM-D. Using the specified dynamics mode, that is, nudging dynamics in the troposphere and stratosphere to meteorological reanalyses, we perform a 1-year-long simulation (July 2009–June 2010) and contrast WACCM-D with the standard WACCM. Both WACCM and WACCM-D simulations are performed with and without forcing from medium-to-high energy electron precipitation, allowing a better representation of the energetic electrons penetrating into the mesosphere. We demonstrate the effects of the strong particle precipitation events which occurred during April and May 2010 on nitric acid and on key ion cluster species, as well as other relevant species of the nitrogen family. The 1-year-long simulation allows the event-related changes in neutral and ionic species to be placed in the context of their annual cycle. We especially highlight the role played by medium-to-high energy electrons in triggering ion cluster chemistry and ion-ion recombinations in the mesosphere and lower thermosphere during the precipitation event, leading to enhanced production of nitric acid and raising its abundance by 2 orders of magnitude from 10−4 to a few 10−2 ppb.
Keywords: Antarktis; elektroner; energiske partikler; geomagnetiske stormer; geovitenskap; ionosfæren; klimamodeller; meteorologi; polarområdene; salpetersyre; stratosfæren

Interhemispheric Survey of Polar Cap Aurora - Reidy, Jade; Fear, Robert; Whiter, Daniel; Lanchester, Betty; Kavanagh, Andrew John; Milan, Steve; Carter, Jennifer; Paxton, Larry; Zhang, Yongliang (Journal of Geophysical Research: Space Physics, 2018)
This study investigates the interhemispheric nature of polar cap auroras via ultraviolet imaging, combined with particle data, to determine whether they occur on open or closed field lines. Data from the SSUSI (Special Sensor Ultraviolet Spectrographic Imager) instrument on board the DMSP (Defence Meteorological Satellite Program) spacecraft are examined. The DMSP spacecraft are in 90-min orbits; hence, images of each hemisphere are separated by 45 min providing a good opportunity for interhemispheric study. 21 polar cap arc (PCA) events are recorded in December 2015 which have particle data from the SSJ/4 particle spectrometer associated with an arc in at least one hemisphere. Nine events are found to contain 'arcs' consistent with a closed field line mechanism, that is, arcs associated with an ion signature present in both hemispheres. Six events contained arcs that were consistent with an 'open field line' mechanism, that is, they were associated with electron-only precipitation. Events containing arcs that were not consistent with either of these expectations are also explored, including an example of a 'non-conjugate' theta aurora and an interesting example of auroral morphology similar to a PCA which is associated with a geomagnetic storm. Seasonal effects are also investigated through a statistical analysis of PCAs over 4 months in 2015. It is found that PCAs are visible in the SSUSI data at least 20% of the time and that it is likely some are missed due to the spacecraft field of view and poor sensitivity in the summer hemisphere due to increased solar illumination.
Keywords: Antarktis; astronomi; energiske partikler; geomagnetiske stormer; meteorologi; polarlys; polarområdene; solvind

Occurrence and average behavior of pulsating aurora - Partamies, Noora; Whiter, Daniel; Kadokura, Akira; Kauristie, Kirsti; Nesse Tyssøy, Hilde; Massetti, Stefano; Stauning, Peter; Raita, Tero (Journal of Geophysical Research: Space Physics, 2017)
Motivated by recent event studies and modeling efforts on pulsating aurora, which conclude that the precipitation energy during these events is high enough to cause significant chemical changes in the mesosphere, this study looks for the bulk behavior of auroral pulsations. Based on about 400 pulsating aurora events, we outline the typical duration, geomagnetic conditions, and change in the peak emission height for the events. We show that the auroral peak emission height for both green and blue emission decreases by about 8 km at the start of the pulsating aurora interval. This brings the hardest 10% of the electrons down to about 90 km altitude. The median duration of pulsating aurora is about 1.4 h. This value is a conservative estimate since in many cases the end of event is limited by the end of auroral imaging for the night or the aurora drifting out of the camera field of view. The longest durations of auroral pulsations are observed during events which start within the substorm recovery phases. As a result, the geomagnetic indices are not able to describe pulsating aurora. Simultaneous Antarctic auroral images were found for 10 pulsating aurora events. In eight cases auroral pulsations were seen in the southern hemispheric data as well, suggesting an equatorial precipitation source and a frequent interhemispheric occurrence. The long lifetimes of pulsating aurora, their interhemispheric occurrence, and the relatively high-precipitation energies make this type of aurora an effective energy deposition process which is easy to identify from the ground-based image data.
Keywords: Antarktis; astronomi; atmosfæren; geofysikk; geomagnetiske stormer; mesosfæren; meteorologi; polarlys

The impact of sunlight on high-latitude equivalent currents - Laundal, Karl M; Gjerloev, Jesper; Østgaard, Nikolai; Reistad, Jone Peter; Haaland, Stein; Snekvik, Kristian; Tenfjord, Paul; Ohtani, Shin-ichi; Milan, Steve (Journal of Geophysical Research: Space Physics, 2016)
Ground magnetic field measurements can be mathematically related to an overhead ionospheric equivalent current. In this study we look in detail at how the global equivalent current, calculated using more than 30 years of SuperMAG magnetometer data, changes with sunlight conditions. The calculations are done using spherical harmonic analysis in quasi-dipole coordinates, a technique which leads to improved accuracy compared to previous studies. Sorting the data according to the location of the sunlight terminator and orientation of the interplanetary magnetic field (IMF), we find that the equivalent current resembles ionospheric convection patterns on the sunlit side of the terminator but not on the dark side. On the dark side, with southward IMF, the current is strongly dominated by a dawn cell and the current across the polar cap has a strong dawnward component. The contrast between the sunlit and dark side increases with increasing values of the F10.7 index, showing that increasing solar EUV flux changes not only the magnitude but also the morphology of the equivalent current system. The results are consistent with a recent study showing that Birkeland currents indirectly determine the equivalent current in darkness and that Hall currents dominate in sunlight. This has implication for the interpretation of ground magnetic field measurements and suggests that the magnetic disturbances at conjugate points will be asymmetrical when the solar illumination is different.
Keywords: Antarktis; geomagnetiske stormer; ionosfæren; ionosfæriske strømmer; polarlys; polarområdene; sollys; solvind

The impact of energetic electron precipitation on mesospheric hydroxyl during a year of solar minimum - Zawedde, Annet Eva; Nesse Tyssøy, Hilde; Hibbins, Robert; Espy, Patrick J; Ødegaard, Linn-Kristine Glesnes; Sandanger, Marit Irene; Stadsnes, Johan (Journal of Geophysical Research: Space Physics, 2016)
In 2008 a sequence of geomagnetic storms occurred triggered by high-speed solar wind streams from coronal holes. Improved estimates of precipitating fluxes of energetic electrons are derived from measurements on board the NOAA/POES 18 satellite using a new analysis technique. These fluxes are used to quantify the direct impact of energetic electron precipitation (EEP) during solar minimum on middle atmospheric hydroxyl (OH) measured from the Aura satellite. During winter, localized longitudinal density enhancements in the OH are observed over northern Russia and North America at corrected geomagnetic latitudes poleward of 55°. Although the northern Russia OH enhancement is closely associated with increased EEP at these longitudes, the strength and location of the North America enhancement appear to be unrelated to EEP. This OH density enhancement is likely due to vertical motion induced by atmospheric wave dynamics that transports air rich in atomic oxygen and atomic hydrogen downward into the middle atmosphere, where it plays a role in the formation of OH. In the Southern Hemisphere, localized enhancements of the OH density over West Antarctica can be explained by a combination of enhanced EEP due to the local minimum in Earth's magnetic field strength and atmospheric dynamics. Our findings suggest that even during solar minimum, there is substantial EEP-driven OH production. However, to quantify this effect, a detailed knowledge of where and when the precipitation occurs is required in the context of the background atmospheric dynamics.
Keywords: Antarktis; astronomi; energiske partikler; geofysikk; geomagnetiske stormer; planetbølger; solvind

Observations of nitric oxide in the Antarctic middle atmosphere during recurrent geomagnetic storms - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Straub, Corinne; Holmén, Kim; Horne, Richard B (Journal of Geophysical Research: Space Physics, 2013)
We report ground-based measurements of the polar middle atmosphere made using a 230–250 GHz passive microwave radiometer deployed at Troll station (72°01′S 02°32′E, L shell of L = 4.8), Antarctica. Our observations show enhanced mesospheric nitric oxide (NO) volume mixing ratio (VMR) during a series of small recurrent geomagnetic storms in the 2008 austral winter, reaching 1.2 ppmv on day 200 (18 July). The Lomb normalized periodogram of the NO VMR time series averaged over 65-80 km for days 130 to 220 of 2008 (9 May to 7 August) shows a peak exceeding the 95% confidence limit at 25.8 days, close to the synodic rotation period for low-latitude solar coronal holes. The highest correlations between the radiometer NO VMR data and trapped and quasi-trapped electron count rates for L = 3.5-5.5 from the Polar Orbiting Environment Satellites 90° telescope are for the >30 keV (90e1) channel (rmax = 0.56, lag time of 5.1 days) and >100 keV (90e2) channel (rmax = 0.57, lag time of 4.4 days). Maximum correlation between NO VMR and the >700 keV (90P6) channel data is lower but lag times are close to zero. Superposed epoch analyses for the eight most significant geomagnetic storm periods and three Carrington rotations (2070-2072) within the 90 day observation period indicate that significant NO abundance observed at 65-80 km in the Antarctic mesosphere may be produced directly by >200 keV electron precipitation or originate from a source at higher altitudes, e.g., production by >30 keV electrons followed by downward transport.
Keywords: Antarktis; atmosfæren; fysikk; geomagnetiske stormer; meteorologi; polarområdene

The effect of energetic electron precipitation on middle mesospheric night-time ozone during and after a moderate geomagnetic storm - Daae, Marianne; Espy, Patrick J; Nesse Tyssøy, Hilde; Newnham, David A; Stadsnes, Johan; Søraas, Finn (Geophysical Research Letters, 2012)
Using a ground-based microwave radiometer at Troll Station, Antarctica (72°S, 2.5°E,L = 4.76), we have observed a decrease of 20–70% in the mesospheric ozone, coincident with increased nitric oxide, between 60 km and 75 km altitude associated with energetic electron precipitation (E > 30 keV) during a moderate geomagnetic storm (minimum Dst of −79 nT) in late July 2009. NOAA satellite data were used to identify the precipitating particles and to characterize their energy, spatial distribution and temporal variation over Antarctica during this isolated storm. Both the ozone decrease and nitric oxide increase initiate with the onset of the storm, and persist for several days after the precipitation ends, descending in the downward flow of the polar vortex. These combined data present a unique case study of the temporal and spatial morphology of chemical changes induced by electron precipitation during moderate geomagnetic storms, indicating that these commonplace events can cause significant effects on the middle mesospheric ozone distribution.
Keywords: Dronning Maud Land; Troll forskningsstasjon; geofysikk; geomagnetiske stormer; mikrobølge; ozonlaget; radiometer

Direct observations of nitric oxide produced by energetic electron precipitation into the Antarctic middle atmosphere - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Holmén, Kim; Horne, Richard B (Geophysical Research Letters, 2011)
We report the first ground-based passive microwave observations made from Troll station, Antarctica, which show enhanced mesospheric nitric oxide (NO) volume mixing ratio reaching levels of 1.2 ppmv, or 2–3 orders of magnitude above background, at 70–80 km during small, relatively isolated geomagnetic storms in 2008. The mesospheric NO peaked 2 days after enhanced NO at higher altitudes (110–150 km) measured by the SABER satellite, and 2 days after peaks in the >30 keV and >300 keV electron flux measured by POES, although the 300 keV electron flux remained high. High time resolution data shows that mesospheric NO was enhanced at night and decayed during the day and built up to high levels over a period of 3–4 days. The altitude profile of mesospheric NO suggests direct production by ∼300 keV electron precipitation. Simulations using the Sodankylä Ion and Neutral Chemistry model show that the delay between thermospheric and mesospheric NO enhancements was primarily a result of the weaker production rate at lower altitudes by ∼300 keV electrons competing against strong day-time losses.
Keywords: Dronning Maud Land; Troll forskningsstasjon; geofysikk; geomagnetiske stormer; meteorologi; observasjoner; radiometer

Some features of electron density behaviour in the high latitude D-region derived from in situ measurements - Danilov, A.D.; Smirnova, N.V.; Blix, Tom Arild; Thrane, E.V.; Vanina, L.B. (Journal of Atmospheric and Solar-Terrestrial Physics, 2003)
A large database of rocket measurements of the D-region electron concentration has been studied. The data were obtained at four sites in the Antarctic (Molodezhnaya and Syowa) and Arctic (Heiss Island, and Andøya/Kiruna). The electron densities were analysed in terms of their variations with solar zenith angle, geomagnetic activity and atmospheric temperature. We found that there is a particle ionisation source in the auroral oval even in quiet conditions. The energy of the particles is such, that they penetrate down to 85km, are partially absorbed between 85 and 80km but do not penetrate (are completely absorbed) below 75km. Analysis of the dependence of the electron concentration [e] on the daily sum of Kp indices, ∑Kp, shows that at all heights considered there is an increase of [e] with ∑Kp up to some saturation value of ∑Kp and beyond this level [e] is either constant (with large scatter of the data) or even decreases. This indicates that when the auroral oval expands with increasing geomagnetic activity, a particular station may move from a position outside or at the boundary of the oval, to a position inside the polar cap. An attempt is made to find the temperature dependence of the electron concentration. It is found that [e] at 75 and 80km increases with temperature T. Analysis of the flights conducted during noctilucent cloud (NLC) events at Andøya/Kiruna reveals a strong dependence of [e] on ∑Kp at 80 and 85km. This dependence is stronger and better defined than that for the entire data set. This may be explained by the low mesopause temperatures observed in summer when NLC occur. A comparison of the electron density data sets with empirical and theoretical models is presented and during quiet magnetic conditions a good agreement with mid-latitude models is found.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene

Electron density variations in the upper D region at high latitudes according to in situ measurements - Danilov, Alexey; Smirnova, N.V.; Vanina-Dart, Liudmila; Blix, Tom Arild; Thrane, Eivind (Geomagnetism and Aeronomy, 2001)
A large set of rocket measurements of the electron concentration [e] in the upper D region at four rocket sites (Molodezhnaya (Antarctic), Heiss Island (Arctic), Syowa (Antarctic), and Andoya/Kiruna (Arctic)) is considered. The dependence of [e] on the solar zenith angle X and geomagnetic activity index ∑Kp is analyzed. It has been shown that, the spread in [e] values reaches two orders of magnitude at any assigned value of χ. Nevertheless, it is possible to draw a lower envelope for the entire set of points and to obtain the [e] variation with χ in undisturbed conditions. In an analysis of the envelopes, it is seen that a corpuscular ionization source (presumably, electrons with an energy of above 40 keV) exists in the nonsunlit D region even in quiet conditions. An analysis of the electron concentration dependence on the daily sum of ∑Kp indices (∑Kp) shows that, at all heights considered, increases [e] with increasing ∑Kp to a certain boundary value ∑Kp and then remains either constant (with a rather wide spread in the data) or even decreases. This saturation effect may be caused by the auroral oval equatorward motion. As a result of this motion the site position may change: it may move toward the boundary between the auroral oval and polar cap or even be within the latter. The slope k of the [e] variation plotted versus ∑Kp at different χ is considered. It is shown that k grows with increasing χ and is maximal at χ> 100°.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene